PENGARUH BEBAN KERJA DAN INSENTIF TERHADAP KINERJA KARYAWAN PADA PT. BPR GEMILANG PERSERODA - Yeni Marlini; Ranti Melasari; Eva Setia Rini Damanik (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis, 2026)
This study aims to analyze the effect of workload and incentives on employee performance at PT BPR Gemilang Perseroda. Employee performance serves as a key indicator of banking operational success, while workload and incentives are considered two primary factors that directly influence employee productivity and work quality. This research employs a quantitative approach with a causal design and census method, involving all 30 employees as the sample. Data were collected through five-point Likert-scale questionnaires and analyzed using validity tests, reliability tests, classical assumption tests, and multiple linear regression with SPSS 27. Results show that: (1) workload has a positive and significant effect on employee performance (t = 2.383; sig. = 0.021); (2) incentives do not have a significant partial effect on employee performance (t = 1.930; sig. = 0.060); and (3) workload and incentives simultaneously have a significant effect on employee performance (F = 15.644; sig. = 0.000), contributing 40.0% of variance (Adjusted R² = 0.374), while the remaining 60.0% is influenced by other variables not examined in this study. These findings imply that proportional workload management is the dominant factor in improving employee performance, while incentive policies need to be revised to be more individually performance-based in order to provide stronger motivational impact. Future studies are recommended to incorporate variables such as leadership, work environment, and work motivation.